The development of an attitude towards risk management in the context of country competitiveness - Stasytytė, Viktorija (Business, Management and Economics Engineering, 2013)
The paper analyses the prevailing definitions of risk, uncertainty and risk management as well as attitudes towards risk identification, analysis and response in the context of the enterprise and country as a whole. The article presents a scheme of attainment of risk-intelligent enterprise management and discloses its application possibilities to country risk management. The paper also shows the schematic views of particular techniques applied in each step of the risk management process. After analysing a report on global country risks, a generalized risk map of global risks is formed and detailed further trends of research are determined in order to develop a thorough picture of country risks in Lithuania.